Comorbidities, mortality and survival in patients with pyoderma gangrenosum: a Danish nationwide registry‐nested case–control study. (27th July 2021) - Ben Abdallah, H.; Bech, R.; Fogh, K.; Olesen, A.B.; Vestergaard, C.
Summary: Background: Pyoderma gangrenosum (PG) is an ulcerative skin disease associated with comorbidities and increased mortality; however, the literature on this topic is scarce. Objectives: To investigate the mortality, prevalence and risk of comorbidities in patients with PG. Methods: This nationwide registry nested case–control study included all inpatients and outpatients diagnosed with PG in tertiary dermatology centres in Denmark between 1 January 1994 and 31 December 2016. Each case was matched on date of birth and sex with 10 unique controls. The Danish National Patient Registry was used to identify all patients and to gather information on comorbidity. Information on age, sex, vital status and emigration was obtained from the Danish Civil Registration System. The outcomes were 19 different comorbidities and all‐cause mortality. Prevalence was assessed from odds ratios (ORs) for specific comorbidities at the time of PG diagnosis. The risk of developing specific comorbidities and death was assessed using hazard ratios (HRs) obtained using the Cox proportional‐hazards model. Results: A total of 1604 patients with PG were matched with 16 039 controls. Some associations were known, e.g. inflammatory bowel disease [OR 19·15 (15·27–24·02), HR 6·51 (4·24–10·01)], while others have not been described previously, e.g. osteoporosis [OR 1·57 (1·22–2·02), HR 2·59 (2·08–3·22)]. Mortality was significantly increased among patients with PG [HR 2·79 (2·57–3·03)]. Conclusions: Patients with PG have increased mortality and an increased prevalence and risk of both previously reported and novel comorbidities that may have severe consequences if left undiagnosed. Our findings are mainly related to moderate and severe PG. Abstract : What is already known about this topic? Pyoderma gangrenosum (PG) is an ulcerative skin disease associated with inflammatory bowel disease, haematological malignancies, rheumatic diseases and increased mortality. What does this study add? The prevalence and risk of previously reported comorbidities to PG were confirmed, and new associations were described. The mortality was threefold higher in patients with PG than in patients without PG. Linked Comment: A.D. Ormerod. Br J Dermatol 2021; 185 :1089–1090 . Plain language summary available online